2020
DOI: 10.1111/cas.14549
|View full text |Cite
|
Sign up to set email alerts
|

Novel cucurmosin‐based immunotoxin targeting programmed cell death 1‐ligand 1 with high potency against human tumor in vitro and in vivo

Abstract: Immunotoxins are Ab‐cytotoxin chimeric molecules with mighty cytotoxicity. Programmed cell death 1‐ligand 1 (PD‐L1), is a transmembrane protein expressed mainly in inflammatory tumor tissues and plays a pivotal role in immune escape and tumor progression. Although PD‐L1 immune checkpoint therapy has been successful in some cases, many patients have not benefited enough due to primary/secondary resistance. In order to optimize the therapeutic efficacy of anti‐PD‐L1 mAb, we used durvalumab as the payload and CUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Results of the cytotoxicity assay in vitro showed that the killing ability of Bs/CUS on different tumor cells was time-dependent under the conditions of 72 and 120 h incubation. This result and incubation time are consistent with the research results of other immunotoxins using CUS as a toxic agent in our laboratory ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Results of the cytotoxicity assay in vitro showed that the killing ability of Bs/CUS on different tumor cells was time-dependent under the conditions of 72 and 120 h incubation. This result and incubation time are consistent with the research results of other immunotoxins using CUS as a toxic agent in our laboratory ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, according to our research, the inhibition might be caused by DVL and thus further increases the drug sensitivity of DTX. The advantages of our HSA-DTX@PEG-DVL NPs in terms of cytotoxicity might be mainly due to cellular uptake superiority and synergy between DVL and DTX, much of the literature also suggested that finding. Consequently, we have shown that the combination of the anticancer drugs DTX and DVL in a single nanoplatform significantly reduces tumor cell progression compared to each drug alone. As a result, our findings suggested that the addition of the DVL mAb on HSA-DTX@PEG-DVL NPs loaded with DTX is a better solution for anticancer efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, the principle of a PD-L1 targeting immunotoxin, based on cucurmosin, has been demonstrated by Zhang et al [51]. As saporin used in our study, cucurmosin is also a type I ribosome-inactivating protein (RIP) that potently inhibits protein synthesis but lacks an effective mechanism to enter cytosol upon endocytosis [52].…”
Section: Discussionmentioning
confidence: 82%